Development of a disuse water sachet lacerating machine; a fibre source for cement composite production (2020)
Disuse water sachet constitutes menace in developing countries; it is abundant, non-biodegradable and the disposal means are expensive, traditional and unhealthy. This paper reports the development of a machine capable of processing water sachets into fibres suitable for cement –composite production. The machine was designed to use fixed spikes and rotary sawing blades for shearing and lacerating the disuse sachets. The blades were rotated by a single phase 2hp electric motor at a speed of 1880 rpm transmitted by means of V-belt pulley system. The machine capacity and lacerating efficiency were 7.5kg/hr and 90.0%, respectively with a production cost of $225. The portable machine is expected to reduce environmental problems and enhance cement – composite properties.